2014
DOI: 10.1063/1.4880204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical (e,2e) studies of tetrahydropyran and 1,4-dioxane

Abstract: We present experimental and theoretical results for the electron-impact ionization of the highest occupied molecular orbitals of tetrahydropyran and 1,4-dioxane. Using an (e,2e) technique in asymmetric coplanar kinematics, angular distributions of the slow ejected electron, with an energy of 20 eV, are measured when incident electrons at 250 eV ionize the target and scatter through an angle of either -10° or -15°. The data are compared with calculations performed at the molecular 3-body distorted wave level. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
3
8
1
Order By: Relevance
“…Note that the M3DW approach has been demonstrated to be quite successful in reproducing collision cross section data for the low and intermediateenergy electron impact ionisation of atoms and molecules. 19 The present work extends our previous results for molecules of some biological interest, such as pyrimidine, 20 tetrahydrofuryl alcohol (THFA), 21,22 tetrahydrofuran (THF), 22, 23 1,4-dioxane, 23,24 and tetrahydropyran (THP). 24 The structure of the present paper is as follows.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…Note that the M3DW approach has been demonstrated to be quite successful in reproducing collision cross section data for the low and intermediateenergy electron impact ionisation of atoms and molecules. 19 The present work extends our previous results for molecules of some biological interest, such as pyrimidine, 20 tetrahydrofuryl alcohol (THFA), 21,22 tetrahydrofuran (THF), 22, 23 1,4-dioxane, 23,24 and tetrahydropyran (THP). 24 The structure of the present paper is as follows.…”
Section: Introductionsupporting
confidence: 84%
“…For θ a = −5 • , we observe excellent agreement in terms of the shape between the distorted wave calculations and the experimental measurement. This result is somewhat surprising in that previously the distorted wave calculations have failed to reproduce the experimental width of the binary feature of other molecular targets [20][21][22][23][24] under this same kinematical condition. However, when we consider the binary regions for the other kinematical conditions of θ a = −10 • or −15 • , we see substantial differences between the experimental data and the distorted wave calculations.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…However we think that it is still of interest to see how good or bad it is since it is very difficult (for us) to get access to enough computer time to perform the proper averages so it would be useful to know if there are cases where it can be used. So far, we have found that it is not good for some intermediate sized molecules [6], [18][19][20], but suprisingly a reasonably good approximation for the big molecules we have examined [21][22][23][24][25].…”
Section: Theoreticalmentioning
confidence: 99%